Arthralgia resolution rate following chikungunya virus infection - Megan O'Driscoll (Elsevier, 2021)
Background: Arthralgia, persistent pain or stiffness of the joints, is the hallmark symptom of chronic chikungunya virus (CHIKV) disease. Associated with significant disability and reduced quality of life, arthralgia can persist for many months following CHIKV infection. Understanding the expected duration of arthralgia persistence is important for managing clinical expectations at the individual-level as well as for estimating long-term burdens on population health following a CHIKV epidemic. Methods: A review of cohort studies reporting the prevalence of arthralgia post-CHIKV infection over multiple time points was conducted. Generalized linear models were used to estimate the average rate of arthralgia resolution following CHIKV infection. Results: Sixteen cohort studies matching the inclusion criteria were identified and included in the analysis. An average rate of arthralgia resolution of 10.85% (95% confidence interval (CI) 9.05–12.66%) per month was estimated across studies, corresponding to an expected median time to arthralgia resolution of 6.39 months (95% CI 5.48–7.66 months) and an expected arthralgia prevalence of 72.21% (95% CI 68.40–76.23%) at 3 months post-CHIKV infection. Conclusions: Estimates of the average rate of arthralgia resolution and the expected prevalence of arthralgia over time post-CHIKV infection were derived. These can help inform expectations regarding the long-term public health burdens associated with CHIKV epidemics.